Delusion, obsession, or both? – Clinical case - Bastos Maia, Francisca; Cordeiro, Filipa; Martins Miranda, Vânia (BIRTH AND GROWTH MEDICAL JOURNAL, 2025)
Introduction: Obsessions and delusions are part of a spectrum of irrational thoughts, with obsessions typically associated with insight and delusions characterized by a lack of insight. However, the concept of "obsessions without insight" has been incorporated into diagnostic criteria in recent years. This case report aims to explore the differential diagnosis between psychosis and obsessive-compulsive disorder (OCD) in an 11-year-old boy. Case description: An 11-year-old boy was admitted to the Child and Adolescent Psychiatry Emergency Department for behavioral changes with four months of evolution. These changes included episodes of aggression toward his mother. In addition, the mother reported that he had developed an obsessive fixation on reading, refused to engage with any form of technology, and reacted angrily when his parents used electronic devices. Conclusion: The overlap between psychotic symptoms and OCD-related symptoms is well documented in the literature and often complicates diagnosis and treatment. In this case, the lack of insight and positive therapeutic response to risperidone supported the diagnosis of psychosis over OCD.